Study on security risks of e-banking system - Gabriela Mogos; Nor Shahida Mohd Jamail (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Online banking and other e-banking modes are a very convenient way to banking in terms of speed, convenience and delivery costs, but they have brought many risks alongside them. Online banking has created a new risk orientation and even new forms of risk. Technology plays an important role as both a source and a tool for risk control. The purpose of this research is to identify the security situation of the e-banking application and to analyze the risks and attacks that could occur to the customers that, although it’s an e-banking application attacks could happen. Several mitigations were mentioned to overcome attacks like, access control is to mitigate eavesdropping this means that, restricting access to sensitive data is mandatory. Another way to mitigate is, update and patch which is for SQL injection meaning, it's vital to apply patches and updates when it’s available. These attacks may attack the whole application or target an individual where private information is stolen or changed. This research also shows how to apply several more different protections measures to protect oneself and organization from being targets of cybercrime.